Status of rpoB gene mutation associated with rifampicin-resistant Mycobacterium tuberculosis isolated in a rural setting in Nepal. Issue 3 (11th March 2021) - Adhikari, Saroj; Saud, Bhuvan; Sunar, Sunil; Ghimire, Sheshraj; Yadav, Bhawani Prasad
Abstract : Mycobacterium tuberculosis ranks among the top 10 causes of deaths in Nepal despite the country having a long history of national tuberculosis prevention programmes that have proved very successful in the control of tuberculosis. Several cases of active or latent tuberculosis are still missing despite that the number of infected individuals is increasing each year. Microscopy has its own limitations and factors like low bacterial load, quality of sample, quality of smear, experience of microscopist etc. influence the overall sensitivity of the test. The implementation of a molecular technique-based rapid, point-of-care testing system offers higher sensitivity in the early diagnosis of tuberculosis. Cepheid GeneXpert is the most commonly used molecular technology in Nepal. It is a cartridge-based semi-quantitative, nested real-time PCR-based diagnostic system. It detects mutations in the beta-subunit of RNA polymerase (rpoB) gene that lead to rifampicin resistance (RR) in M. tuberculosis complex. The present study aims to increase our understanding of the epidemiology of mutations in the rpoB gene in tuberculosis-positive patients by using the Xpert MTB/RIF assay in a rural setting in Pyuthan Hospital, Nepal. Sputum from 2733 patients was tested for the diagnosis of tuberculosis using the Cepheid GeneXpert system between July 2018 and January 2020 at Pyuthan Hospital. Two hundred and ninety-seven of these samples (10.86 %) were positive for M. tuberculosis, of which 3.3 % (10/297) were rifampicin-resistant. Among rifampicin-resistant tuberculosis (RR-TB) patients, 50.0 % (5/10) showed mutations located in codons 529–533 (probe E) of the rpoB gene, followed by others. The GeneXpert system can be a convenient, highly sensitive, rapid and accurate tool for the diagnosis of tuberculosis, also identifying RR-TB and at the same time determining the molecular epidemiology of rifampin resistance-associated mutations in rural and/or resource-limited laboratory settings.